555 ADHERENCE AND PERSISTENCE OF PCSK9 INHIBITORS IN CLINICAL PRACTICE: THE REAL-WORLD ITALIAN EXPERIENCE (AT-TARGET-IT STUDY). (15th December 2022) - Marzano, Federica; Basile, Christian; Paolillo, Stefania; Cesaro, Arturo; Buonocore, Davide; Asile, Gaetano; Abbate, Vincenza; Vicidomini, Francesca; Maria Spaccarotella, Carmen Anna; Spirito, Giulio; Maloberti, Alessandro; Iannuzzo, Gabriella; et al.
Abstract: Introduction: Hypercholesterolemia is a major risk factor for the development of atherosclerotic cardiovascular disease (ASCVD). Proprotein Convertase Subtilisin/Kexin type 9 inhibitors (PCSK9i) are recommended in patients with documented ASCVD or Familial Hypercholesterolaemia (FH), not achieving LDL-C target while treated with maximally tolerated dose of lipid-lowering therapy (LLTs). In this conext, single country real-life data, reporting use of PCSK9i in clinical practice are needed. Purpose: AT-TARGET-IT is an observational, retrospective, IV phase registry, involving 10 Italian sites, designed to study adherence and persistence of PCSK9i (either Evolocumab or Alirocumab) in patients with ASCVD or FH. Methods: All clinical and demographic characteristics were recorded at the time of first prescription and at the latest observation preceding inclusion in the study. Adherence was calculated as Medical Possession Ratio (MPR), defined as the ratio between the drug units dispensed during the treatment period and the duration of the treatment period itself. Persistence was defined as therapeutic continuity from the start of treatment upon enrollment and was assessed at the time points of 6, 12 and 18 months from prescription. Results: 798 patients were enrolled. In the overall population, mean age was 62 years (±7.8) and the majority were male (66%). Patients were followed for a median time of 19.33 months. 760 patients (95.2%) showed high adherence to therapy, 13 (1.6%) partial adherence, and 25 (3.1%) no adherence. At 6 month 99.7% of patients enrolled in the study remained on therapy; there were 519 and 423 patients in the study with a follow up of at least 12 and 18 months respectively. Persistence in these groups was 98.1% and 97.5%, respectively. Overall, 28 patients (3.5%) discontinued therapy. No differences in adherence and persistence were found between patients on Alirocumab or Evolocumab. Conclusion: The AT-TARGET-IT registry study demonstrated that, in a large single-country real-world population, PCSK9i therapy is extremely successful in routine clinical practice, very high adherence and persistence.